Kesesuaian Lahan Tambak Garam Di Desa Siduwonge Kecamatan Randangan Kabupaten Pohuwato - Nurul Auliyah; Muhlis Latjolai (Gorontalo Fisheries Journal, 2019)
The purpose of this research is to analyze suitability salt pond in the Siduwonge Village, Randangan Distric, Pohuwato Regency. This research used spatial analysis and laboratory test to know salt qualities. Result of this research show that salt from Siduwonge Village is quite suitable for use as consumption salt and industrial salt. Spatial analysis of salt ponds found that salt fields area belong to S1 category was ±183 ha, salt fields area belong to S2 category was ±1,109 ha and area belong to N category was 6,652 ha.